Processing-optimized reactive polymer compositions

By introducing an appropriate amount of silane modification into the polypropylene copolymer, a hot melt adhesive preparation with a melt viscosity between 500 mPas to 4500 mPas and a melt enthalpy of 20 J/g to 35 J/g was prepared, which solved the problem of low melt viscosity of silane graft polymers in the prior art, achieved good processability and mechanical stability, and was suitable for the bonding of a variety of substrates.

CN117580877BActive Publication Date: 2025-05-02CLARIANT INT LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202280046099.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-07-01
Filing Date
2022-06-13
Publication Date
2025-05-02
Estimated Expiration
2042-06-13

AI Technical Summary

Technical Problem

In the prior art, silane grafted polymers have too low melt viscosity at high temperatures, resulting in unsuitable in many application fields; at the same time, in order to adjust viscosity and adhesiveness, a large number of tackifiers and low viscosity components are usually required, limiting the scope of use.

Method used

By modifying the polypropylene copolymer, the silicon content between 1% and 5%, the melt viscosity at 170°C is between 500 mPas to 4500 mPas, the melt enthalpy between 20 J/g and 35 J/g, combined with an appropriate amount of reactive silylated components, a hot melt adhesive preparation with good processability and mechanical stability is prepared.

Benefits of technology

Hot melt adhesive with good processability at low temperatures is achieved, the dependence on tackifier is reduced, the cohesiveness, heat resistance and elongation of break are improved, and it is suitable for bonding of various substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004634897120000121
    Figure BDA0004634897120000121
  • Figure BDA0004634897120000131
    Figure BDA0004634897120000131
  • Figure BDA0004634897120000141
    Figure BDA0004634897120000141
Patent Text Reader

Abstract

The present invention relates to silane-modified polypropylene copolymers having a silicon content between 1% and 5% by weight, a melting enthalpy between 20 J / g and 35 J / g, and a melt viscosity at 170° C. between 500 mPas and 4500 mPas. The present invention also relates to processing-optimized reactive hot melt adhesive formulations containing these silane-modified polypropylene copolymers, and the use of these hot melt adhesive formulations for bonding various substrates. The present invention also relates to a process for preparing these silane-modified polypropylene copolymers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to silane-modified polypropylene copolymers having a silicon content between 1% and 5% by weight, a melting enthalpy between 20 J / g and 35 J / g, and a melt viscosity at 170° C. between 500 mPas and 4500 mPas. The present invention also relates to a processing-optimized reactive hot melt adhesive formulation comprising the silane-modified polypropylene copolymer, and to the use of the hot melt adhesive formulation for bonding various substrates. The present invention also relates to a method for preparing these silane-modified polypropylene copolymers. Background Art

[0002] Semi-crystalline polyalphaolefins serve in many cases as raw materials for widely used adhesives. The fields of use extend from the hygiene sector to laminating and packaging adhesives to applications in building adhesives and wood processing.

[0003] By grafting with agents capable of crosslinking, such as alkoxysilanes, the cohesion, adhesion, mechanical stability and heat resistance of unmodified poly-α-olefins can be altered because the macromolecular properties are altered by crosslinking the polymer chains with each other, and the grafted alkoxysilanes can also covalently introduce reactive surface groups (e.g. -OH) into the bond.

[0004] The free-radical-induced grafting of semicrystalline poly-α-olefins with silane groups leads to chain degradation in the ungrafted polymer, often only very low functionalization rates being achieved, and to the formation of grafted products having a highly waxy character (eg WO 89 / 11513) which appear to be unsuitable for stable adhesion.

[0005] This also applies to free radical-induced grafting reactions of polypropylene or propylene-rich copolymers, where chain scission reactions are likewise known to occur, thereby reducing the molar mass of the polymer (and thus also the melt viscosity). Therefore, corresponding polymers with a high degree of functionalization inevitably have very low molar mass / melt viscosity and are not suitable for many fields of application.

[0006] Furthermore, the subsequent crosslinking of the degraded chains by silane groups leads to changes in the mechanical properties, which in extreme cases can result in a hard, high-strength material with a low brittle temperature.

[0007] WO 2007 / 008765 (Dow) describes the use of low-viscosity, silane-grafted poly(ethylene-co-1-olefin) polymers as adhesive raw materials. The polymers used for modification have an ethylene content of at least 50 mol % ethylene, and a polydispersity of preferably 1 to 3.5, wherein the entire range is reported to be 1 to 5. They show a low melt viscosity of a minimum of 2,000 and a maximum of 50,000 cP at 177°C. As 1-olefin comonomers, many higher 1-olefins, such as 1-hexene and 1-octene, are particularly included. Silane-grafted polymers have low failure temperatures in PAFT and SAFT analyses. The use of polyolefins with a high ethylene content inevitably means the presence of long ethylene blocks in the polymer. This in turn leads to poor wetting and adhesion properties on many plastic surfaces, so that very many bonding problems cannot be optimally solved. In addition, long polyethylene sequences tend to crosslink peroxidically, which leads to the inevitable formation of gels. The ungrafted base polymer has a relatively low molar mass and a melt viscosity of a maximum of 50,000 cP at 177°C.

[0008] The use of crystalline and semi-crystalline poly (propylene-to-1-olefin) polymers is also described, which are also considered suitable for grafting. These have a propylene content of at least 50 mol %, and preferably a melt viscosity of 50,000 cP at 170 ° C (before and after grafting) and a polydispersity of 1 to 3.5. The crystallinity is reported to be 2-60% (i.e., 3-100 J / g). However, there is no example designated as these preferred polypropylene-based copolymers. There is no other research on the polymer with a melting enthalpy between 20 J / g and 35 J / g and a viscosity between 500 mPas and 4500 mPas. Therefore, WO 2007 / 008765 neither takes a specific combination of features as a subject, nor takes the resulting favorable processing properties and adhesion properties as a subject.

[0009] EP0827994 (Huels) describes the use of silane-grafted amorphous poly(α-olefins) as moisture-crosslinkable adhesive raw materials or adhesives. As base polymers, random polypropylene (aPP), random poly(1-butene) or preferably copolymers or terpolymers of C4-C10 α-olefins (0-95 wt. %), propylene (5-100 wt. %) and ethylene (0-20 wt. %) are used. The silane-modified APAO terpolymer shown in the examples has a softening point of 98° C., a weight-average molecular weight of 38,000 g / mol and a melt viscosity of 6000 mPas. Grafting leads to a reduction in PDI of more than 35% and a reduction in viscosity of 88%. The combination of mechanical properties and processing properties is not explored in detail.

[0010] DE 103 38 344 A1 (Clariant) relates to semicrystalline polyolefin homopolymers or copolymers free-radical modified with silane compounds, whose viscosity measured at 170° C. is between 10 mPas and 50,000 mPas and whose heat of fusion is greater than 10 J / g. The examples disclose polyolefins whose melt viscosity at 170° C. is less than 1000 mPas, whose dropping point exceeds 110° C. and whose heat of fusion is at least 60 J / g. They are suitable as ingredients for hot melt adhesive formulations. The combination of low melt viscosity and heat of fusion between 20 J / g and 3535 J / g is not disclosed.

[0011] The silane-modified crystalline polyolefin wax is prepared by means of metallocene catalysis and has a high propylene content.

[0012] In the case of hot melt adhesive formulations containing silane-modified polyolefins, the bonding process is two-stage. In order to avoid processing problems and to ensure simple application, technicians are looking for hot melt adhesive formulations with low viscosity so that the hot melt adhesive can be applied with pressure at relatively low temperatures. Once the adhesive is applied, crosslinking begins, thereby increasing the viscosity and building up the cohesion of the bond, which should ensure the mechanical stability of the final bond.

[0013] However, it should be taken into account here that very low-viscosity products with viscosities below 8,000 mPas are generally insufficient in terms of mechanical properties, such as elastic modulus, strength and elongation at break, since due to the very short chain lengths there are fewer polymer entanglements (tangles) and the product is more likely to have waxy properties. In addition, due to the very short chain lengths, the material becomes brittle quickly when crosslinked, since the short polymer chains that are crosslinked to each other have only low flexibility. Therefore, the prior art teaches away from the use of very low-viscosity base polymers and recommends the use of larger amounts of tackifiers in combination with higher-viscosity silanized polyolefins.

[0014] Adhesive tackifiers affect the viscosity of the adhesive as well as the initial adhesion and are typically resins. These resins are low molecular weight products such as C5 or C9 streams from crude oil processing, typically contain aromatics, and typically have a glass transition temperature above room temperature.

[0015] Therefore, mixing resins into hot melt adhesive formulations increases the glass transition temperature of the formulation, so that the corresponding hot melt adhesive suffers from reduced low temperature flexibility and the temperature range in which the hot melt adhesive can be used is limited.

[0016] WO2010018027A1 (Evonik) describes silane-modified polypropylene copolymers and terpolymers with a high degree of functionalization and a maximum poly(ethylene) triad content of 2.5% by weight, a melting enthalpy of 9-20 J / g and a xylene solubility of more than 96% by weight; wherein the best results can be achieved with terpolymers comprising ethylene and 1-butene. For various adhesives containing these modified polyolefins, many example formulations are mentioned. These formulations do provide relatively good mechanical stability after bonding, but in order to ensure good processing properties and sufficient initial viscosity, a relatively large amount of tackifier is required. It is reported that in the example formulations for edge gluing, the minimum share of modified polyolefins in the formulation is 24.7% by weight. All other examples contain 30% by weight or more.

[0017] In addition, WO2010018027A1 teaches that the peroxide-induced grafting reaction further reduces the polydispersity of the polymers used, and from this it is concluded that the modified polymers have a polydispersity significantly less than 3.5, which is said to lead to various disadvantages in terms of processing properties, among other things. In addition, the document teaches that the use of relatively low molecular weight base polymers generally leads to relatively low functionalization rates.

[0018] EP 3287276 A1 (Sika) describes hot melt adhesive compositions comprising silane-modified polyalphaolefins which are solid at 25° C., non-modified amorphous C3 / C2 copolymer waxes having a softening temperature of <120° C., and paraffin waxes having a softening point of 80-130° C. The adhesive composition contains various silane-modified polyalphaolefins, wherein their sum in the formulation is >55% by weight.

[0019] WO2009133093 (Sika) describes a hot melt adhesive composition with an extended open time, which comprises a silane-modified polyalphaolefin that is solid at 25° C. and a soft resin with a melting point or softening point of 10-40° C. The examples of the formulations contain 65% by weight of silane-modified polyalphaolefins. The proportion of all silane-grafted polyalphaolefins is greater than 50% by weight, preferably between 60% and 90% by weight.

[0020] It is therefore found that it is usually necessary to add relatively large amounts of tackifiers and low-viscosity components to silane-modified adhesive formulations in order to adjust the viscosity for processing and the initial tack of the adhesive. Without this addition, the silanized polyolefins have high viscosities, which limit the range of use and bring additional process-related and material-specific problems to the adhesive formulator. Therefore, adhesive formulators are constantly looking for solutions that are suitable for balance, widespread use, require as few individual components as possible, and minimize the share of functional additives.

[0021] Therefore, there is a need for functionalized polyolefins as and for hot melt adhesive materials that can be easily processed and applied due to their improved material properties even at low temperatures (below 170° C.) without having to use too much resin or tackifier, and still being able to achieve sufficient initial adhesion and flexible and stable bonding, and high heat resistance of the hot melt adhesive. Summary of the invention

[0022] Surprisingly, it has been found that silane-modified polypropylene copolymers with a silicon content of between 1% and 5% by weight, based on the total amount of the modified polymer, a melt viscosity of greater than 500 mPas and less than 4500 mPas at 170° C., a melting enthalpy of greater than 20 J / g and less than 35 J / g, preferably greater than 20 J / g and less than 30 J / g, as hot melt adhesives or as a component of hot melt adhesive formulations, impart extremely advantageous properties to the formulations, which are reflected in particular in their improved processability. Copolymers in the sense of the present invention are polymers composed of two or more different types of monomer units. Silane-modified polypropylene copolymers include as a further monomer one or more monomers selected from ethylene and 1-butene, wherein binary copolymers are preferred, and ethylene is particularly preferred as a comonomer in addition to propylene.

[0023] Silane-modified polypropylene copolymers lead to both very good processability and very good mechanical properties of the adhesive, which can be described qualitatively and quantitatively by good cohesion, adhesion, heat resistance and elongation at break of the hotmelt adhesive. Here, a lower proportion of reactive silanized components is required in the formulation in order to achieve the same required properties of the hotmelt adhesive in terms of heat resistance, cohesion, elongation at break, etc., compared with conventional formulations. The advantageous properties of the hotmelt adhesive are particularly evident on polar substrates. DETAILED DESCRIPTION

[0024] The modification of the unmodified polypropylene copolymer is carried out by grafting. Side reactions may occur during grafting, which lead in particular to chain scission of the grafted polymer, so that grafting and modification are to be considered synonymous in the present application.

[0025] In addition to the described silicon content between 1% by weight and 5% by weight, a melt viscosity of more than 500 mPas and less than 4500 mPas at 170° C. and a melting enthalpy of more than 20 J / g and less than 35 J / g, preferably more than 20 J / g and less than 30 J / g, the silane-modified polypropylene copolymer preferably has a melt viscosity of between 10% and 50% of the initial viscosity of the unmodified polypropylene. The corresponding percentage change in the melt viscosity makes possible a combination of particularly easy processability and good mechanical stability due to the correct degree of crosslinking.

[0026] The silane to be grafted preferably has an olefinic double bond and one to three alkoxy groups bonded directly to the silicon atom. In particular, one or more silanes are selected from the group consisting of vinyltrimethoxysilane (VTMO), vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, 3-methacryloxypropyltrimethoxysilane (MEMO; H2C═C(CH3)COO(CH2)3-Si(OCH3)3), 3-methacryloxypropyltriethoxysilane, vinyldimethylmethoxysilane and / or vinylmethyldibutoxysilane. Very particularly preferably, the silane is vinyltrimethoxysilane.

[0027] In order to adjust the desired mechanical properties, it is advantageous if the polypropylene copolymer backbone of the silane-modified polypropylene copolymer has a weight average molecular weight measured according to ISO 16014-1 of greater than 10,000 and less than 30,000 g / mol, preferably greater than 10,000 and less than 20,000 g / mol, because within this molecular weight range the polymer chains are sufficiently functionalized and can therefore be stably crosslinked, but they still have sufficient flexibility.

[0028] Preferably, the silane-modified polypropylene copolymer has a polydispersity index (PDI) of less than 2.5. Preferably, this is increased due to grafting and the increase relative to the ungrafted polymer is at least 20%. Due to this change in the grafted PDI, it is apparent that only in the case of silane-modified polypropylene-based copolymers, free radical-induced chain degradation occurs to an extent that leads to a sufficient reduction in viscosity, but this extent is still small enough to allow subsequent crosslinking to reach an extent that ensures both high flexibility of the bonds and sufficient strength of the bond. This increase in PDI is completely surprising, since free radical-induced chain degradation usually leads to a reduction in PDI.

[0029] Preferably, the silane-modified polypropylene copolymer has a softening point between 85° C. and 95° C. The silane-modified polypropylene copolymer having a softening point within this range has sufficiently good properties both for heat resistance and for processability.

[0030] In addition, the silane-modified polypropylene copolymer preferably has a molecular weight greater than 0.900 g / cm 3 density.

[0031] Preferably, the silane-modified polypropylene copolymer has a propylene content of mm triads in the range of 90 mol% or less and at least 5 mol% of rr triads. The silane-modified polypropylene copolymer having the microstructure exhibits desirable processing properties and mechanical properties.

[0032] In a preferred embodiment, the silane-modified polypropylene copolymers are prepared with the aid of metallocene catalysts.

[0033] In a preferred embodiment, the unmodified reactant of the silane-modified polypropylene copolymer has a propylene content of at least 60 mol %, particularly preferably between 70 mol % and 90 mol %. Within this range, the comonomer has a sufficiently large content to prevent embrittlement of the material, but not so large that the adhesive properties are reduced due to an excessively high ethylene content.

[0034] Particularly preferably, the unmodified reactant of the silane-modified polypropylene copolymer has 13 A propylene fraction of at least 60 mol % propylene determined by C NMR.

[0035] Furthermore, another subject of the present invention is a process for preparing a silane-modified polypropylene copolymer according to claim 1, comprising the following steps:

[0036] a) providing a polypropylene copolymer,

[0037] b) adding a grafting component and a free radical initiator,

[0038] c) evaporating excess monomer,

[0039] The invention is characterized in that, compared with the starting product, the grafting reaction causes the melt viscosity of the grafted product to be reduced by 50-90% and the PDI to be increased by at least 20%.

[0040] Preferably, in the process according to the invention, an unmodified polypropylene copolymer is used which has a melt viscosity measured at 170° C. according to DIN 53019 of between 500 and 7,000 mPas, preferably between 700 and 5,000 mPas, particularly preferably between 800 and 4,000 mPas, and a melting enthalpy measured according to ISO 11357-3 of between 30 and 55 J / g, preferably between 30 and 50 J / g, particularly preferably between 30 and 45 J / g.

[0041] Another subject of the present invention is a hot melt adhesive formulation comprising a silane-modified polypropylene copolymer according to the invention and one or more base polymers selected from the group consisting of unmodified polyolefins and unmodified thermoplastic styrene block copolymers (TPE-S), wherein the silane-modified polypropylene copolymer and the base polymer constitute at least 50% by weight of the hot melt adhesive formulation, and up to 30% by weight of the silane-modified polypropylene copolymer is used, based on the total weight of the hot melt adhesive formulation.

[0042] The unmodified polyolefin is preferably a crystalline or semi-crystalline polyolefin or an amorphous polyolefin (APAO), ethylene-vinyl acetate copolymer (EVA) and polyisobutylene (PIB), wherein the polyolefin is particularly preferably formed from a C3 / C2 copolymer, and the unmodified styrene block copolymer is preferably SBS, SEBS, SEPS, SEEPS and MBS.

[0043] Preferably, the hot melt adhesive formulation has a melt viscosity of less than 5000 mPas measured at 170° C. in accordance with DIN 53019 and a tensile strength of at least 4 MPa, since hot melt adhesives having these properties constitute an optimum between processability and mechanical stability.

[0044] The hotmelt adhesive formulations according to the invention can contain synthetic and / or natural resins, in particular adhesive resins, synthetic and / or natural oils, inorganic and / or organic, synthetic and / or natural polymers, which can optionally be conductive or insulating.

[0045] In particular, the hot melt adhesive formulation according to the present invention comprises a tackifying resin (tackifier), wherein the resin is used to adjust the specific properties of the adhesive layer, especially the viscosity and / or adhesion, the flow behavior and creep behavior and / or the adhesive viscosity of the adhesive layer, to meet special requirements. These can be natural resins and / or synthetic resins. In the case of natural resins, these natural resins contain abietic acid (e.g. rosin) as a main component. In addition, the resin can be a terpene resin or a polyterpene resin, a petroleum resin and / or a coumarin-indene resin, wherein especially the so-called C5 resin and / or the C9 resin and / or the copolymer of the C5 / C9 resin.

[0046] The proportion of tackifier in the hotmelt adhesive according to the invention is up to 35% by weight of tackifier, based on the total formulation, particularly preferably between 1% by weight and 30% by weight, and particularly preferably between 3% by weight and 20% by weight, since the preferred viscosity of the hotmelt adhesive for processing can also be achieved with small amounts of resin, and these amounts in the hotmelt adhesive according to the invention are sufficient to ensure adequate initial adhesion.

[0047] The hot melt adhesive according to the present invention may contain other ingredients required to achieve specific properties, such as deformability, tack, processability, crosslinking rate, crosslinking density, (melt or solution) viscosity, strength, crystallization rate, viscosity, storage stability, etc.

[0048] Particularly preferably, the hot melt adhesive formulation comprises, based on its total mass, 40-80 wt % of base polymer, 10-30 wt % of polypropylene copolymer and 10-30 wt % of tackifier. In the case of formulations with these weight ratios, the preferred properties are exhibited in an optimal manner and a hot melt adhesive with particularly balanced property characteristics is provided.

[0049] In a particular embodiment of the invention, the proportion of the other components is particularly preferably at most 10% by weight. This has the advantage that the material properties of the adhesive preparation are essentially the same as the material properties of the polymer used according to the invention. Such an adhesive preparation can be produced with very little effort.

[0050] Further ingredients may be crosslinking accelerators, in particular silanol condensation catalysts, inorganic and / or organic fillers which may be optionally conductive or insulating, inorganic and / or organic pigments which may be optionally conductive or insulating, inorganic and / or organic, synthetic and / or natural fibers which may be optionally conductive or insulating, inorganic and / or organic stabilizers and / or inorganic and / or organic flame retardants.

[0051] In an alternative embodiment, the silane-modified polypropylene copolymer or the hot melt adhesive formulation comprises a crosslinking accelerator present in an amount of 0.1 to 1 wt %, based on the total amount of the mixture of the silane-modified polypropylene copolymer and the crosslinking accelerator or the hot melt adhesive formulation.

[0052] This is particularly preferred when the polymers according to the invention are used in adhesive bonds whose maximum durability is to be achieved within a short time after bonding.

[0053] Suitable crosslinking accelerators are various compounds, in particular Brønsted acids and / or Lewis acids, for example acetic acid, itaconic acid, zinc(II) acetate, cadmium acetate, zinc oxide, zinc stearate, zinc(II) chloride, tin(IV) chloride, dibutyltin oxide, dibutyltin dilaurate, bismuth citrate, bismuth(III) oxide, bismuth titanate, tetrabutylgermanium, tetrabutyltin, titanium boride, titanium(IV) oxide, titanium acetylacetonate, tributyl titanate, sodium chloride, magnesium(II) chloride, zinc acetylacetonate, zinc methacrylate, zinc niobate, tin(II) oxide, tin(IV) oxide, zirconium(IV) acetylacetonate, zirconium(IV) oxide and / or zirconium(IV) silicate.

[0054] Measurement method:

[0055] The polyolefins listed were characterized according to the standards listed. Non-standard characterization was performed as described.

[0056] The weight average and number average molecular weight M of the copolymer w and M n The determination is carried out in 1,3-o-dichlorobenzene and calibrated with PP. The measurement is carried out by gel permeation chromatography at a temperature of 135° C. The determination is carried out in accordance with ISO 16014-1.

[0057] The softening point is measured according to ASTM D 3104.

[0058] Density was determined according to ISO 1183-3:1999.

[0059] The melt viscosity is determined according to DIN 53019 as follows:

[0060] The liquid to be tested is located in the annular gap between two coaxial cylinders, one of which rotates at a constant speed (rotor) and the other is stationary (stator). The speed and torque required to overcome the frictional resistance of the liquid in the annular gap are determined.

[0061] The shear stress and velocity gradient present in the liquid can be calculated from the geometrical dimensions of the system and the determined torque and speed values.

[0062] This standard describes the standard flow chart for measuring the flow behavior of Newtonian and non-Newtonian liquids in a rotational viscometer with coaxial cylinders by specifying specific geometric ratios. Since the reactants and the silane-modified products are structurally viscous liquids, the dynamic viscosities of three measurements at 170°C at different shear rates (shear rate 1: 192 1 / s, shear rate 2: 318 1 / s, shear rate 3: 532 1 / s) are averaged.

[0063] According to ISO 11357-3 and ISO 113572, the melting enthalpy and glass transition temperature are measured by differential calorimetry (DSC). At a heating rate of 10 K / min, the melting range of the melting enthalpy, glass transition temperature and crystalline part is measured by DSC from the second heating curve. The turning point in the heat flow curve is evaluated as the glass transition temperature. In the present case, the analysis of the modified polymer is always carried out in the non-crosslinked state without additives, wherein during the measurement, it is meaningful to cover with dry protective gas or inert gas (e.g., nitrogen, argon, etc.).

[0064] The polydispersity index PDI is calculated from the weight average molecular weight M w and number average molecular weight M n The quotient is calculated and determined according to standard ISO16014-1.

[0065] The silicon content was determined photometrically on a Perkin-Elmer Lambda 35 photometer from Perkin Elmer.

[0066] For this purpose, the sample to be analyzed is decomposed as follows: Depending on the Si content, 0.1-0.15 g of polymer is weighed into a platinum crucible and 0.5 ml of concentrated sulfuric acid is added. The liquid is evaporated off on a hot plate and then ashed in a muffle furnace at 600° C. for 1.5 to 2 hours to form sulfated ash. Subsequently, the sulfated ash is decomposed in a flame with as little sodium carbonate as possible, filtered off from the platinum crucible with Millipore water and rinsed into a 100 ml plastic volumetric flask.

[0067] To determine the silicon content of the sample thus decomposed photometrically, 10 ml of the decomposed solution were pipetted into a 50 ml plastic volumetric flask and admixed with 5 ml of 2M sulfuric acid to adjust the pH. 10 ml of molybdate reagent were then added and the solution was made up to 50 ml with Millipore water.

[0068] Prior to the measurement, the photometer was calibrated according to the following procedure: a calibration series with a concentration of 0, 1, 2, 4, 5 mg Si / l was pipetted from the stock solution into 50 ml flasks. To adjust the pH, 5 ml of 2M sulfuric acid was added. Thereafter, 10 ml of molybdate reagent was added and the calibration solution was transferred to the corresponding cuvette. After 2 to 10 minutes in the photometer, the samples of the calibration series were calibrated at a wavelength of 400 nm. To verify the calibration, an external control standard with a concentration of 5 mg Si / l was similarly processed and measured in the photometer.

[0069] The solution of the sample to be determined for silicon content is transferred to a cuvette and measured after 2 to 10 minutes in a photometer at a wavelength of 400 nm.

[0070] Adhesion is determined as lap shear strength in a tensile shear test according to DIN EN 1465.

[0071] Before sample preparation, all specimens used are cleaned and dust-free. In addition, all plastic and glass specimens are degreased with a suitable cleaning agent before sample preparation. The specimens are subsequently bonded in accordance with DIN EN 1465. All specimens prepared in this way are stored in a climate cabinet at 20°C and 50% relative humidity for 14 days before use. This achieves a uniform water content, for example in the case of wood specimens. This eliminates or minimizes individual effects caused by elevated humidity, for example in the case of hydrophilic or hydrolysis-sensitive polymers.

[0072] The cohesion is determined as the tensile strength in a tensile test in accordance with DIN EN ISO 527-3.

[0073] With the help of 13 C NMR determines the propylene fraction and the PP triad, with quantification being carried out by integration of the characteristic signals:

[0074] The data were recorded on a Varian Mercury-VX 400 (9.4 Tesla) NMR spectrometer with the aid of a 5 mm sampling head (nuc4, 13C sensitive). 13 C NMR spectroscopy. 13 C NMR measurements (Lamor frequency: 100.62 MHz) were performed under quantitative conditions, i.e., using an inverse gated pulse sequence. The other parameters were as follows: spectral width: 25 kHz; recording time: 1.3 s; relaxation delay: 20 s; number of scans: about 4000; excitation angle: 90°; measurement temperature: 80°C.

[0075] For this purpose, in each case about 50 mg of the EP copolymer was dissolved in 0.7 ml of solvent (20% C6D6 / 80% 1,2,4-trichlorobenzene) and homogenized.

[0076] The triad fractions were calculated based on Markov probability statistics suitable for PP / PE copolymers.

[0077] The elongation at break of the hot melt adhesive according to the present invention is determined in accordance with ISO 527, except that a non-standard specimen produced by melt pressing is used in each case, which is different in size from the standard specimen. The specimens used to measure strength and elongation at break have the following dimensions: total length: 50 mm, narrow portion width: 3.3 mm, end width: 7 mm, narrow parallel portion length: 25 mm, thickness: 1 mm.

[0078] The elongation at break corresponds to the tensile strength at break and is determined by a tensile strain test in accordance with ISO 527. The force per unit area (given in MPa) required to break the test specimen is determined here. The tensile test is carried out in accordance with ISO 527, except for the test specimen.

[0079] The invention is illustrated in detail by the following examples and claims.

[0080] Example

[0081] Embodiment design:

[0082] For the grafting of polypropylene copolymers prepared with the metallocene catalysts listed in columns 2 and 3 of Table 1, 500 g of each polypropylene copolymer were melted under nitrogen blanket in a glass apparatus equipped with stirrer, internal thermometer and distillation bridge. In columns 4 to 6 are the available data for non-grafted comparative polyolefins from the prior art.

[0083] Table 1

[0084]

[0085] At a temperature of 160° C., over the course of 3 h, 50 g of trimethoxyvinylsilane (10% based on the amount of polymer used) were metered in continuously from the metering funnel, while 10 g of di-tert-butyl peroxide were simultaneously added continuously from the second dropping funnel. After the metering addition was complete, a further 1.1 g of di-tert-butyl peroxide were metered into the reaction mixture and the reaction was continued at 160° C. for 1 h.

[0086] A vacuum (about 30 mbar) was subsequently applied and the volatile fractions were distilled off. After about 30 min, the pressure was vented to normal pressure by introducing nitrogen.

[0087] The properties of the resulting modified products are reported in columns 2 and 3 of Table 2. In columns 4 to 6 available data for grafted polyolefins from the prior art can be found.

[0088] Table 2

[0089]

[0090] Preparation of hot melt adhesive formulations and bonding of various substrates

[0091] To prepare the hot melt adhesive formulation according to the invention, a melt mixture of the silane-modified polypropylene copolymer and the other components specified in Table 3 in the weight proportions specified therein was prepared by hot melt mixing (approximately 180° C.) using a propeller stirrer.

[0092] Table 3

[0093]

[0094]

[0095] In the above hot melt adhesive formulations, it can be seen in the case of Examples 2, 5 and 8 according to the invention that, with the low viscosity of the formulation, high cohesion (tensile strength), elongation at break, heat resistance and adhesion (lap shear strength) can be achieved on various substrates, especially on wood. When using silane-modified polypropylene copolymers as the only component of the hot melt adhesive, the silane-modified components according to the invention are significantly better than the comparative examples on wood. Even on polypropylene (PP) and ABS, the components according to the invention in pure form show good adhesion and are significantly improved in terms of cohesion compared to Comparative Examples 1 and 3.

[0096] These properties, which are already favorable in pure form, show their full potential in the formulation. Compared with comparative examples 4, 6, 7 and 9, examples 5 and 8 according to the invention have much lower viscosities at the same concentration of the reaction components in the formulation, which significantly improves and extends the processing range for the user, and additionally show much higher heat resistance as well as significantly improved cohesion, adhesion and elongation at break.

Claims

1. Silane-modified polypropylene copolymers containing ethylene and / or 1-butene as comonomers and having a photometrically determined silicon content of between 1% and 5% by weight, based on the total mass of the polymer, a melt viscosity measured at 170° C. in accordance with DIN 53019 of more than 500 mPa•s and less than 4500 mPa•s and a melting enthalpy measured in accordance with ISO 11357-3 of more than 20 J / g and less than 35 J / g, It is characterized in that The silane-modified polypropylene copolymer has a polydispersity index of less than 2.5 measured according to standard ISO 16014-1, and the polydispersity index is increased due to grafting relative to the unmodified polypropylene copolymer, wherein the increase is at least 20% of the initial value; The unmodified reactants have 13 a propylene fraction of at least 60 mol % propylene as determined by C NMR, and The polypropylene copolymer backbone has a weight average molecular weight greater than 10,000 and less than 30,000 g / mol measured according to ISO 16014-1.

2. The silane-modified polypropylene copolymer according to claim 1, characterized in that It has a melting enthalpy measured according to ISO 11357-3 of greater than 20 J / g and less than 30 J / g.

3. The silane-modified polypropylene copolymer according to claim 1 or 2, characterized in that: The melt viscosity of the silane-modified polypropylene copolymer, measured according to DIN 53019, is between 10% and 50% of the initial viscosity of the unmodified polypropylene copolymer.

4. The silane-modified polypropylene copolymer according to claim 1 or 2, characterized in that: The polypropylene copolymer backbone has a weight average molecular weight greater than 10,000 and less than 20,000 g / mol measured according to ISO 16014-1.

5. The silane-modified polypropylene copolymer according to claim 1 or 2, characterized in that: It has a softening point measured according to ASTM D 3104 between 85°C and 95°C.

6. The silane-modified polypropylene copolymer according to claim 1 or 2, characterized in that: It has a density greater than 0.900 g / cm³ measured according to ISO 1183-3:1999.

7. The silane-modified polypropylene copolymer according to claim 1 or 2, characterized in that: With the help of 13 The propene content determined by C NMR is 90 mol % or less of mm triads and at least 5 mol % of rr triads.

8. The silane-modified polypropylene copolymer according to claim 1 or 2, characterized in that: The silane-modified polypropylene copolymer contains the crosslinking accelerator in an amount of 0.1 to 1 wt % based on the total amount of the mixture of the silane-modified polypropylene copolymer and the crosslinking accelerator.

9. A method for preparing a silane-modified polypropylene copolymer according to any one of claims 1 to 8, comprising the following steps: a) providing an unmodified polypropylene copolymer, b) adding a silane grafting component and a free radical initiator, and c) evaporating excess monomer, Characterized in that the grafting reaction leads to a reduction of the melt viscosity measured at 170° C. in accordance with DIN 53019 by 50 to 90% relative to the initial viscosity of the unmodified polypropylene copolymer and an increase of the polydispersity index determined in accordance with standard ISO 16014-1 by at least 20%.

10. The method according to claim 9, characterized in that The unmodified polypropylene copolymer has a melt viscosity of between 500 and 7,000 mPa·S measured at 170° C. according to DIN 53019 and a melting enthalpy of between 30 and 55 J / g measured according to ISO 11357-3.

11. The method according to claim 10, characterized in that The unmodified polypropylene copolymers have a melt viscosity measured at 170° C. according to DIN 53019 of between 700 mPa·S and 5000 mPa·S.

12. The method according to claim 10, characterized in that The unmodified polypropylene copolymers have a melt viscosity, measured at 170° C. in accordance with DIN 53019, of between 800 mPa·S and 4,000 mPa·S.

13. A hot melt adhesive formulation comprising a silane-modified polypropylene copolymer according to any one of claims 1 to 8 and one or more base polymers selected from non-modified polyolefins and non-modified, thermoplastic styrene block copolymers, wherein these components together constitute at least 50% by weight of the hot melt adhesive formulation, and up to 30% by weight of the silane-modified polyolefin is used, based on the total weight of the hot melt adhesive formulation.

14. The hot melt adhesive preparation according to claim 13, characterized in that: The thermoplastic styrene block copolymer is TPE-S.

15. The hot melt adhesive preparation according to claim 13 or 14, characterized in that: It has a viscosity of less than 5000 mPa·s at 170° C., measured in accordance with DIN 53019, and a tensile strength of at least 4 MPa, measured in accordance with DIN EN ISO 527-3.

16. The hot melt adhesive preparation according to claim 13 or 14, characterized in that: It contains less than 35% tackifier, based on the total mass of the hot melt adhesive formulation.

17. The hot melt adhesive preparation according to claim 16, characterized in that: It contains 40-80 wt % of a base polymer, 10-30 wt % of a silane-modified polypropylene copolymer and 10-30 wt % of a tackifier, based on the total mass of the hot melt adhesive formulation.

18. The hot melt adhesive formulation according to claim 13, 14 or 17, characterized in that: The hot melt adhesive formulation contains a crosslinking accelerator in an amount of 0.1 to 1 wt % based on the total amount of the hot melt adhesive formulation.

19. Use of a silane-modified polypropylene copolymer according to any one of claims 1 to 8 or of a hot melt adhesive formulation according to any one of claims 13 to 18 for bonding substrates.

Citation Information

Patent Citations

  • Modified polyolefin waxes

    DE10338344A1

  • Use of grafted amorphous poly-alfa-olefins as moisture-curable raw material for adhesives and as adhesives

    EP0827994A2

  • Reactive polyolefin hot-melt adhesive with lower reactivation temperature and use thereof in deep draw vacuum lamination

    EP3287276A1

  • Adhesive compositions

    WO1989011513A1

  • Silane-grafted olefin polymers, compositions and articles prepared therefrom, and methods for making the same

    WO2007008765A2